A relação entre vontade e representação na estética de Nietzsche e Schopenhauer - Gildete dos Santos Freitas (2015)
The aim of this research is to investigate the reception of the concept of Will in the context of Nietzsche´s so called first period. I will be trying to identify the aspects of his first works which could be described as an intended criticism directed against Schopenhauer’s notion of Will. Indeed, the aesthetic program put forward by Nietzsche in the Birth of Tragedy relies broadly on the Schopenhauerian conceptual framework, more specifically on the dichotomy between Will and representation, whose terms are translated into the mythical vocabulary of the Apollonian and the Dionysian duality, which are described by Nietzsche as the original artistic drives whose activity was directly responsible for the dynamics of the Greek artistic achievements from the beginning on. The culminating point of this narrative is the Greek tragedy, which is presented by Nietzsche not only as an artistic genre, but also and more crucially as a metaphysical experience. In Nietzsche’s account of the Greek aesthetic experience of the tragic, the apollonian drive plays a role similar to that played by the Schopenhauerian principle of reason in the constitution of the world as representation. In the Birth of Tragedy, Apollo is the mythical name for the principle of the beautiful appearance, which is conceived by Nietzsche as a device concealing the terrifying truth of a Dionysian Will devouring itself incessantly. Dionysius it the wild deity, whose symbolism helps Nietzsche to convey the untamable strength of nature and the fugacity of the individuals. Nietzsche came to his famous dictum that the existence as well as the world only can be justified as an aesthetic phenomenon through his meditation on the peculiar way the Greeks found to deal with the pessimistic truth expressed by the Dionysian myth. This metaphysical thesis gains expression through the mysterious conceptual figure of the primordial unity, announced in The Birth of Tragedy as “the eternal suffering and full of contradiction”, which urges for getting rid from its pain and contradiction through the appearances. What is implied in this context, so the argument, is the idea that the appearance is not restricted to the Apollonian element, but includes also its opposite aspect, the Dionysian dimension of the natural drives. In order to argue for the thesis of a crucial conceptual reformulation of the Schopenhauerian conceptual framework by the young Nietzsche, on needs to reconsider the essence/appearance dichotomy taking as reference the category of the primordial unity (Ur-Eine), through which Nietzsche conceives the Apollonian and the Dionysian as phenomenal instances corresponding to proper aesthetic worlds emerging from the primordial pain. The primordial Unity category is the key that allows us to properly understand the claim Nietzsche raises in The Birth of Tragedy, according to which the Apollonian and the Dionysian drives should be thought of as co-pertaining to the primordial unity.